SIMPLEKS METHOD FOR BIOBJECTIVE LINEAR PROGRAMMING - RYAN ARDIAN (NIM: 10114091), ALFONSUS
Optimization is one of the main component in industrial world. Optimization can be used to maximize profit, minimize waste, maximize selling price and others. Real world problem usually have two or more objective functions, but the commonly studied optimization is optimization with a single objective function. In this final project, it will be discussed about how to solve linear optimization problem with two objective functions or usually called biobjective linear programming for two cases. The first case is minimizing waste and maximizing profit of a shoes company, while the second case is minimizing production cost and maximizing selling price of a peanut trade company. The methods used in this final project are Simplex Method to find the optimal solution and Branch and Bound Method to get the optimal solution in integer form.